DEVELOPMENT OF SKIN ANTI-POLLUTION FILM-FORMING SPRAY - Wacharalertvanich, Rinlada; Aimwattana, Racheeda; Panraksa, Pattaraporn; Jantrawut, Pensak (Thai Bulletin of Pharmaceutical Sciences, 2021)
The aim of this study was to develop topical skin anti-pollution film-forming spray by simple solution method. The film-forming sprays were developed using 2 types of hydroxypropyl methylcellulose (HPMC E5 and E15) and plasticizers (polyethylene glycol: PEG; propylene glycol: PG; glycerin:G). Biosaccharide gum (1% w/v), which is an active ingredient, was used. The film-forming sprays composed of a film-forming polymer i.e. HPMC E5 or HPMC E15 (2% w/v) along with PEG, PG, and G (0.2% w/v) showing good film appearance and short skin evaporation time were subjected to the evaluation of parameters related to formulation and container. The results revealed that the film-forming spray composed of 2% w/v of HPMC E5 and 0.2% w/v PG (E5-PG) gave non-sticky, clear, colorless film with a smooth surface. The evaporation times of E5-PG tested on skin and bagasse paper were 4.28 and 14.33 min, respectively. The viscosity of E5-PG formulation was 10.55 mPa·s. The formulation could be sprayed with a high spray coverage area of 71.70 cm2. The volume of solution delivered upon each actuation and spray angle of E5-PG were 139.8 µL and 79.80 degrees, respectively. In addition, E5-PG showed percentages of fine particulate matter protection property at 93.84 and 63.57% compared to the control 1, which had no barrier, and control 2, which had filter cloth as a barrier, respectively. In the skin irritation study conducted on 30 human volunteers, E5-PG did not cause any irritation. In conclusion, E5-PG has the potential for use as an anti-pollution film-forming spray.